Cu-doped Bi2O2CO3 nanosheet catalyst as well as preparation method and application thereof
The one-step hydrothermal method of Cu-doped Bi2O2CO3 nanosheet catalyst was prepared, and the problem of poor catalyst selectivity and stability in electrocatalytic carbon dioxide reduction reaction was solved, and efficient carbon dioxide reduction to formic acid was achieved, becoming a cheap and environmentally friendly high-performance catalyst.
Patent Information
- Application Number
- CN202411479954.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing electrocatalytic carbon dioxide reduction reaction catalysts have poor selectivity and stability, unclear catalyst structure and unclear catalytic mechanism, which limits the large-scale application of electrocatalytic carbon dioxide reduction reactions.
The Cu-doped Bi2O2CO3 nanosheet catalyst was synthesized by a one-step hydrothermal method, using acetic acid and ammonia as solvents to control the hydrothermal reaction conditions, and a quadrangium nanosheet catalyst with regular shape and uniform size was prepared, which significantly improved the selection of carbon dioxide reduction to formic acid. Sex and stability.
It realizes high performance and efficient production of catalysts, becoming a cheap alternative to precious metals and heavy metal catalysts, significantly enhancing catalytic activity and stability, and is suitable for large-scale production.
Smart Images

Figure CN119287438A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic carbon dioxide reduction, and specifically relates to a Cu-doped Bi2O2CO3 nanosheet catalyst and a preparation method and application thereof. Background Art
[0002] Since the Industrial Revolution, excessive carbon dioxide has been discharged with the overuse of fossil fuels. The carbon dioxide that nature cannot recycle and consume has led to serious ecological problems such as global warming, desertification and ocean acidification, which have had a significant impact on the natural environment and human development, and gradually threatened the sustainable development of society. Therefore, it is of great practical significance to explore new artificial carbon cycles and efficiently convert and utilize CO2 through new and green methods. At the same time, reducing greenhouse gas emissions and lowering the level of CO2 in the atmosphere has become a broad consensus of the international community.
[0003] In recent years, with the increasing maturity of green renewable energy technologies such as solar energy, wind energy, geothermal energy and nuclear energy, the status of renewable energy in human daily production and life has become more and more important, and the electricity obtained from renewable energy has become cheaper and more efficient. In this context, the use of renewable electricity to electrocatalytically reduce carbon dioxide to organic small molecules with higher energy density, such as carbon monoxide, methane, methanol, formic acid and ethylene, can not only store the electricity generated by intermittent renewable energy in the form of stable chemical energy for a long time, but also realize the closed carbon cycle utilization, which is a solution that kills two birds with one stone. The electrochemical CO2 reduction reaction (CO2RR) has the advantages of high reaction rate, adjustable selectivity, relatively easy reaction system under ambient conditions, and potential integration with renewable electricity for power supply. It has shown great application potential and commercial value and has attracted much attention.
[0004] However, the current electrocatalytic carbon dioxide reduction reaction still faces problems such as poor catalyst selectivity and stability, unclear catalyst structure, and unclear catalytic mechanism. Cheap and high-performance electrocatalysts for carbon dioxide reduction are still relatively scarce, which limits the large-scale application of the electrocatalytic carbon dioxide reduction reaction. Summary of the invention
[0005] The present invention provides a Cu-doped Bi2O2CO3 nanosheet catalyst, a preparation method and an application thereof. The catalyst is a tetragonal nanosheet with regular shape and uniform size, which is obtained by a one-step hydrothermal method, has excellent selectivity and good stability for electrocatalytic reduction of carbon dioxide to formic acid, and has excellent performance. The preparation method is simple, the raw material cost is low, the yield is high, and it is easy to mass produce.
[0006] The technical solution of the present invention is: In the first aspect, a Cu-doped Bi2O2CO3 nanosheet catalyst is disclosed. The nanosheet catalyst is synthesized by mixing Cu salt and Bi salt in a precursor solution through a hydrothermal method. The nanosheet catalyst is represented by the (011) and (110) crystal planes of Bi2O2CO3.
[0007] Preferably, acetic acid, ammonia water and water are used as solvents, two metal salts of copper nitrate and bismuth nitrate are dissolved simultaneously in the solvent, and Cu-doped Bi2O2CO3 nanosheet catalyst is synthesized by hydrothermal method, and then the Cu-doped Bi2O2CO3 nanosheet catalyst powder is obtained by centrifugation, washing and drying.
[0008] In a second aspect, a method for preparing a Cu-doped Bi2O2CO3 nanosheet catalyst comprises the following steps: 1) Stir water, acetic acid and ammonia water in a reaction container to form a mixed solution 1, weigh copper nitrate and bismuth nitrate, add them to the mixed solution 1, and stir to form a mixed solution 2; 2) The mixed solution 2 is transferred to a reactor, and the reactor is placed in an oven for hydrothermal reaction. After the hydrothermal reaction, the mixture is naturally cooled, centrifuged, washed, and dried; 3) Take out the dried solid, grind it, and obtain Cu-doped Bi2O2CO3 nanosheet catalyst powder.
[0009] Preferably, in step 1), the volume ratio of water, acetic acid and aqueous ammonia is 2:(0.9-1.1):(5.9-6.1), and the molar ratio of copper nitrate to bismuth nitrate is 0.5-4:1.
[0010] Preferably, in step 2), the hydrothermal reaction temperature is 175-185° C. and the reaction time is 11.5-12.5 h.
[0011] Preferably, in step 2), water is used for washing, and the drying is performed at 55-65° C. and in an oven for 10-12 hours.
[0012] In a third aspect, the application of the Cu-doped Bi2O2CO3 nanosheet catalyst in electrocatalytic carbon dioxide reduction is disclosed.
[0013] Preferably, the Cu-doped Bi2O2CO3 nanosheet catalyst is used for electrocatalytic reduction of formic acid with carbon dioxide in neutral, alkaline and acidic electrolytes.
[0014] In the preparation method of the present invention, ammonia water and acetic acid play an important role. Acetic acid is used as a carbon source, and the pH value of the precursor solution is regulated by adding ammonia water. Bismuth oxycarbonate cannot be synthesized without ammonia water in the precursor solution, and other substances are generated; the precursor solution containing only ammonia water can synthesize bismuth oxycarbonate, but its crystallinity is poor, and the catalyst is in the form of large flakes, which are thick and not very regular.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses non-precious metals Cu and Bi as raw materials and successfully synthesizes Cu-doped bismuth carbonate nanosheet catalysts through a simple one-step hydrothermal reaction, which completely changes the morphology of the catalyst, significantly increases the surface area of the catalyst, and greatly improves the selectivity of carbon dioxide reduction to formic acid. Tests show that the product has excellent catalytic activity and catalytic stability, becoming a cheap and environmentally friendly alternative to precious metal and heavy metal catalysts.
[0016] (1) The present invention directly mixes two metal salts in a precursor solution, successfully synthesizes a Cu-doped bismuth oxycarbonate catalyst by a one-step hydrothermal method, and limits the type and pH of the solvent for the hydrothermal reaction, as well as the hydrothermal reaction time, to generate nanosheets with a specific morphology. The synthesis method is simple, and the single synthesis amount is very considerable, enabling gram-level production.
[0017] (2) Cu is doped into bismuth oxycarbonate, and the bismuth oxycarbonate is transformed from the original nanoflower morphology to a uniform nanosheet morphology, which further exposes a large number of active sites and significantly enhances the catalytic activity of the material; (3) The raw materials for material synthesis are widely available, cheap, highly controllable, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figure is a flow chart of the preparation of the Cu-doped BOC electrocatalyst of the present invention.
[0019] Figure 2 : a is a comparison chart of the XRD of the Cu-doped BOC catalyst prepared in Example 1 of the present invention and the BOC catalyst prepared in Comparative Example 1 with a bismuth oxycarbonate standard card; b is a comparison chart of the XRD of the catalysts synthesized in Comparative Examples 2-4 using only acetic acid as solvent, only ammonia water as solvent and water as solvent with the Cu-doped BOC catalyst.
[0020] Figure 3 : a is a scanning electron microscope image of the BOC sample catalyst prepared in Comparative Example 1 of the present invention, b is a scanning electron microscope image of the Cu-doped BOC sample catalyst prepared in Example 1 of the present invention, c is a transmission electron microscope image of the Cu-doped BOC sample catalyst prepared in Example 1 of the present invention, and d is a high-resolution transmission electron microscope image of the Cu-doped BOC sample catalyst prepared in Example 1 of the present invention.
[0021] Figure 4: a is a comparison of the Bi 4f fine XPS spectra of the Cu-doped BOC catalyst prepared in Example 1 of the present invention and the BOC catalyst prepared in Comparative Example 1, and b is a Cu 2p fine XPS spectrum of the Cu-doped BOC prepared in Example 1.
[0022] Figure 5 Figures ad are SEM images of the catalysts prepared at different hydrothermal times in Comparative Examples 5-8.
[0023] Figure 6 The working curves of the catalytic activity of carbon dioxide reduction in 0.5 M KHCO3 solution are shown in Example 4 using the Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) prepared in Example 1 and in Comparative Example 14 using the bismuth oxycarbonate nanosheet prepared in Comparative Example 1.
[0024] Figure 7 : a is a Faraday efficiency diagram of formic acid product when the BOC catalyst in Comparative Example 15 is tested by chronoamperometry, and b is a Faraday efficiency diagram of formic acid product when the Cu-doped BOC catalyst in Example 5 of the present invention is tested by chronoamperometry.
[0025] Figure 8 It is a point-line comparison diagram of the Faraday efficiency of formic acid product when the catalysts synthesized at different hydrothermal times in Comparative Examples 16-18 of the present invention are tested by chronoamperometry.
[0026] Fig. 9 This is a point-line comparison diagram of the Faraday efficiency of formic acid products when different metal-doped bismuth oxycarbonate catalysts in Comparative Examples 19-23 of the present invention are tested by chronoamperometry.
[0027] Fig.10 : ac are respectively the Faraday efficiency diagrams of the electrocatalytic carbon dioxide reduction of formic acid products in neutral, alkaline and acidic electrolytes during the constant current test in Example 6 of the present invention, and d is the carbon dioxide reduction stability test diagram during the electrochemical chronoamperometry test in Example 7 of the present invention. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0029] Example 1 This embodiment provides a preparation method of Cu-doped Bi2O2CO3 nanosheet catalyst. The preparation process diagram is shown in FIG. Figure 1 As shown, the preparation method is specifically as follows: 1) Take 2 mL of acetic acid, 4 mL of ultrapure water and 12 mL of ammonia water and mix them evenly to form a mixed solution 1. Weigh 2 mmol of copper nitrate trihydrate and 2 mmol of bismuth nitrate pentahydrate and add them to the mixed solution 1. Stir for 30 minutes to form a mixed solution 2. 2) Transfer the mixed solution 2 to a 25mL hydrothermal reactor and react at 180°C for 12h. After cooling to room temperature, take out the reactor. Transfer the solution and precipitate in the reactor to a centrifuge tube, wash three times with distilled water, and keep the precipitate and dry it in a 60°C oven for 12h. 3) Grinding to obtain Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) powder.
[0030] The catalyst powder prepared in this example was subjected to XRD test. Figure 2 As shown in Figure 2, XRD showed that 23.9 and 32.7 correspond to (011) and (110) crystal planes, respectively. The XRD of Cu-doped BOC catalyst is highly consistent with the standard card of Bi2O2CO3 (PDF#41-1488), proving that Bi2O2CO3 was successfully synthesized. The SEM, TEM and HRTEM images of the catalyst are shown in Figure 2. Figure 3 As shown, Figure 3 b and 3c are the scanning electron microscope images and transmission electron microscope images of the Cu-doped BOC catalyst, respectively. It can be seen that the catalyst has a tetragonal nanosheet morphology with uniform thickness and a size of about 900nm. Figure 3 d is a high-resolution transmission electron microscopy image of the Cu-doped BOC catalyst. Through the measurement of the crystal lattice, it was found that 0.356nm and 0.254nm correspond to the (011) and (110) crystal planes of BOC, which corroborates the XRD pattern. The XPS spectrum of the catalyst is shown in Figure 4 As shown, Figure 4 The lower figure in a is the Bi 4f fine XPS spectrum of the Cu-doped BOC catalyst prepared in Example 1 of the present invention, Figure 4 b is the Cu 2p fine XPS spectrum of the Cu-doped BOC catalyst, which can prove the presence of the Cu element in the Cu-doped BOC catalyst and prove that Cu is successfully doped into BOC.
[0031] Comparative Example 1 The difference from Example 1 is that copper nitrate trihydrate is not added in step 1), and the other preparation steps are the same to prepare bismuth oxycarbonate nanosheets (BOC). Figure 2As shown in a, the XRD of the BOC catalyst is highly consistent with the standard card of Bi2O2CO3 (PDF#41-1488), proving that Bi2O2CO3 was successfully synthesized. 3a is a scanning electron microscope image of the BOC catalyst, and it can be observed that the BOC catalyst presents a three-dimensional morphology of nanosheet stacking. At the same time, the corresponding (011) and (110) crystal planes in the XRD of the BOC and Cu-doped BOC catalysts were finely analyzed and found that compared with the BOC catalyst, the Cu-doped BOC catalyst shifted to a higher angle, indicating that the introduction of Cu caused the lattice compression strain of BOC. The Bi 4f fine XPS spectrum is shown in Figure 4 As shown in a.
[0032] Example 2 This embodiment provides a preparation method of a Cu-doped Bi2O2CO3 nanosheet catalyst, and the specific preparation method is as follows: Take 2mL of acetic acid, 4mL of ultrapure water and 12mL of ammonia water and mix them evenly to form mixed solution 1. Weigh 2mmol of copper nitrate trihydrate and 2mmol of bismuth nitrate pentahydrate and add them to mixed solution 1. Stir for 30min to form mixed solution 2. Transfer mixed solution 2 to a 25mL hydrothermal reactor and react at 175℃ for 12h. After it cools to room temperature, take out the reactor. The solution and precipitate in the reactor were transferred to a centrifuge tube, washed three times with distilled water, and the precipitate was kept and dried in an oven at 55°C for 12 h, and ground to obtain Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) powder.
[0033] Example 3 This embodiment provides a preparation method of a Cu-doped Bi2O2CO3 nanosheet catalyst, and the specific preparation method is as follows: Take 2mL of acetic acid, 4mL of ultrapure water and 12mL of ammonia water and mix them evenly to form mixed solution 1. Weigh 2mmol of copper nitrate trihydrate and 2mmol of bismuth nitrate pentahydrate and add them to mixed solution 1. Stir for 30min to form mixed solution 2. Transfer mixed solution 2 to a 25mL hydrothermal reactor and react at 185℃ for 12h. After it cools to room temperature, take out the reactor. The solution and precipitate in the reactor were transferred to a centrifuge tube, washed three times with distilled water, and the precipitate was kept and dried in an oven at 65°C for 12 h, and ground to obtain Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) powder.
[0034] Comparative Example 2 The difference from Example 1 is that no ammonia water is added in step 1), and the other preparation steps are the same as those in Example 1. The XRD pattern of the prepared material is as follows: Figure 2As shown in b, it can be seen from the figure that the BOC material was not successfully synthesized.
[0035] Comparative Example 3 The difference from Example 1 is that acetic acid is not added in step 1), and the other preparation steps are the same as those in Example 1. The XRD pattern of the prepared material is as follows: Figure 2 As shown in b, the BOC material was synthesized but the crystallinity was poor.
[0036] Comparative Example 4 The difference from Example 1 is that in step 1), acetic acid and ammonia water are not added, only 8 mL of ultrapure water is added, and the other preparation steps are the same as those in Example 1. The XRD pattern of the prepared material is shown in FIG. Figure 2 As shown in b, the BOC material was not successfully synthesized.
[0037] Comparative Example 5 Different from Example 1, step 2) of this comparative example does not include a hydrothermal reaction, and a precipitate is generated during the stirring of the mixed solution 2. The precipitate is transferred to a centrifuge tube, washed three times with distilled water, and the retained precipitate is placed in a 60° C. oven for drying for 12 h. The other preparation steps are the same as those of Example 1. Figure 5 a is a scanning electron microscope image of the comparative example, showing the morphology of bonded nanoblocks.
[0038] Comparative Example 6 The difference from Example 1 is that the hydrothermal reaction time in step 2) is 1 h, and the other preparation steps are the same as those in Example 1. Figure 5 b is a scanning electron microscope image of the comparative example, showing the stacked assembly morphology of the nanosheets.
[0039] Comparative Example 7 The difference from Example 1 is that the hydrothermal reaction time in step 2) is 4 h, and the other preparation steps are the same as Example 1. Figure 5 c is a scanning electron microscope image of the comparative example, showing the stacked assembly morphology of the nanosheets, with the nanosheets slightly enlarged.
[0040] Comparative Example 8 The difference from Example 1 is that the hydrothermal reaction time in step 2) is 8 hours, and the other preparation steps are the same as Example 1. Figure 5 d is the scanning electron microscope image of the comparative example, showing the stacked assembly morphology of the nanosheets, and the thickness of the nanosheets increased.
[0041] Comparative Example 9 The difference from Example 1 is that in step 1), "2 mmol copper nitrate trihydrate" is replaced by "2 mmol indium nitrate", and the other preparation steps are the same as those in Example 1.
[0042] Comparative Example 10 The difference from Example 1 is that in step 1), "2 mmol copper nitrate trihydrate" is replaced by "2 mmol iron nitrate nonahydrate", and the other preparation steps are the same as those in Example 1.
[0043] Comparative Example 11 The difference from Example 1 is that in step 1), "2 mmol copper nitrate trihydrate" is replaced by "2 mmol cobalt acetate tetrahydrate", and the other preparation steps are the same as those in Example 1.
[0044] Comparative Example 12 The difference from Example 1 is that in step 1), "2 mmol copper nitrate trihydrate" is replaced by "2 mmol zinc acetate dihydrate", and the other preparation steps are the same as Example 1.
[0045] Comparative Example 13 The difference from Example 1 is that in step 1), "2 mmol copper nitrate trihydrate" is replaced by "2 mmol tin acetate", and the other preparation steps are the same as Example 1.
[0046] Example 4 In order to explore the application of the Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) prepared in this application in the electrocatalytic reduction of carbon dioxide, the following research was carried out: The Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) prepared in Example 1 and the bismuth oxycarbonate nanosheet prepared in Comparative Example 1 were used to perform the measurement, and a working curve of the carbon dioxide reduction catalytic activity in a 0.5 M KHCO3 solution was drawn: (1) The three-electrode system was used to test the Cu-doped Bi2O2CO3 nanosheet catalyst and the bismuth oxycarbonate nanosheet (BOC) catalyst. The catalyst was prepared into 5 mg mL-1 with ultrapure water and anhydrous ethanol. -1 The ink is added with Nafion as a binder and applied on a 1cm 2 The carbon paper was loaded with 1 g cm -2 , the baked carbon paper is clamped on the electrode clamp as the working electrode, and then the platinum electrode is used as the auxiliary electrode, and the Ag / AgCl electrode is used as the reference electrode; (2) The material properties were tested by linear sweep voltammetry with the initial voltage set at -0.6 V, the end voltage at -2.6 V, and the scan rate at 10 mV·s. -1 , two working curves were recorded in Ar and CO2 saturated electrolytes respectively. The results are shown in Figure 6Compared with the two environments of Ar and CO2 saturated electrolyte, the current density of Cu-doped BOC and BOC catalysts under CO2 saturated conditions is larger, indicating that they have the ability to electrocatalyze carbon dioxide reduction; and, when the same voltage is applied in CO2 saturated solution, the current density of Cu-doped BOC is significantly larger than that of BOC, proving that Cu-doped BOC has better activity in electrocatalytic CO2 reduction.
[0047] Comparative Example 14 Different from Example 4, the Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-dopedBOC) prepared in Example 1 is replaced by the bismuth oxycarbonate nanosheet (BOC) prepared in Comparative Example 1. The working curve is as follows: Figure 6 shown.
[0048] Example 5 The catalytic activity of the above catalyst for carbon dioxide reduction in 0.5 M KHCO3 solution confirmed that the Cu-doped Bi2O2CO3 nanosheet catalyst prepared in Example 1 of the present invention has the ability to catalyze carbon dioxide reduction. The following method is now used to explore the performance of the catalyst in carbon dioxide reduction to generate formic acid in an H-type electrolytic cell.
[0049] The Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) and bismuth oxycarbonate nanosheet (BOC) prepared in Example 1 were used to perform the measurement and draw a Faraday efficiency diagram of carbon dioxide reduction to generate formic acid in an H-type electrolytic cell: ① The electrochemical workstation was used to test the three-electrode system. The Cu-doped Bi2O2CO3 nanosheet catalyst and BOC catalyst were configured to 5 mg mL -1 Ink, drop on 1cm 2 The carbon paper was loaded with 1 g cm -2 , the baked carbon paper is clamped on the electrode clamp as the working electrode, and then the platinum electrode is used as the auxiliary electrode, and the Ag / AgCl electrode is used as the reference electrode; ② The chronoamperometry was used to test the performance of the material in catalyzing carbon dioxide to generate formic acid. The product distribution of the catalyst was mainly analyzed. The gas product was determined by online gas phase (GC) and the liquid product was determined by nuclear magnetic resonance. The step voltage was set from -0.65V to -1.65V, and the reaction was performed for 30 minutes at each voltage. The working curve was recorded and the gas product was detected by gas phase during the reaction. A trace amount of electrolyte was taken to detect the liquid product. Substitute it into the formula:
[0050] Where V is the volume of the cathode electrolyte, C is the HCOO after electrolysis measured by NMR -concentration, n is the number of transferred electrons of a specific product (n = 2 for HCOOH), and F is the Faraday constant (96500C mol −1 ), Q is the total charge consumed in the electrolysis process, and the Faraday efficiency of formic acid of the catalyst at each voltage is calculated. The results are as follows Figure 7 As shown in b.
[0051] Comparative Example 15 The difference from Example 4 is that in this comparative example, the Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) prepared in Example 1 is replaced by the bismuth oxycarbonate nanosheet (BOC) prepared in Comparative Example 1. The test results are as follows: Figure 7 As shown in a.
[0052] Depend on Figure 7 It can be seen that the formic acid Faradaic efficiency of the Cu-doped catalyst is significantly improved compared with that of BOC. Within the voltage range of 900 mV, the formic acid Faradaic efficiency of the Cu-doped BOC catalyst is above 90%, and even within the range of -0.85~-1.15 V (relative to the standard hydrogen electrode), the formic acid Faradaic efficiency reaches 95%, showing that the Cu-doped BOC catalyst has good catalytic reduction performance of carbon dioxide to produce formic acid.
[0053] Comparative Examples 16-18 Different from Example 4, the Cu-doped Bi2O2CO3 nanosheet catalyst prepared in Example 1 was replaced with the catalysts prepared in Comparative Examples 6-8, and a Faraday efficiency diagram of carbon dioxide reduction to formic acid in an H-type electrolytic cell was plotted, as shown in FIG. Figure 8 As shown, the catalyst hydroheated for 12 h has the highest Faradaic efficiency for producing formic acid in the entire measured voltage range.
[0054] Comparative Examples 19-23 Different from Example 4, the Cu-doped Bi2O2CO3 nanosheet catalyst prepared in Example 1 was replaced with the catalysts prepared in Comparative Examples 9-13, and a Faraday efficiency diagram of carbon dioxide reduction to formic acid in an H-type electrolytic cell was plotted, as shown in FIG. Fig. 9 As shown, the Cu-doped BOC catalyst significantly improves the Faraday efficiency of bismuth oxycarbonate to formic acid, and improves the performance of the catalyst; the incorporation of In also slightly improves the performance of bismuth oxycarbonate, but not as great as that of Cu, but indium as a precious metal will greatly increase the production cost; the incorporation of Co and Zn has no obvious effect; the incorporation of Fe and Sn reduces the performance of bismuth oxycarbonate, indicating that not all metal doping can prepare catalysts with excellent catalytic performance, and the realization of the doping performance of Cu in the present invention also requires specific synthesis conditions.
[0055] Example 6 In order to further explore the performance of the catalyst prepared by the present invention in reducing carbon dioxide to generate formic acid in an electrolyte.
[0056] The Cu-doped Bi2O2CO3 nanosheet catalyst (Cu-doped BOC) prepared in Example 1 was used for measurement, and the Faraday efficiency diagrams of the reduction of carbon dioxide to formic acid in neutral, alkaline and acidic electrolytes in the flow cell were drawn respectively: ① Use an electrochemical workstation to test with a three-electrode system and configure the catalyst to 5 mg·mL -1 Ink, dripped on 4 cm 2 The carbon paper was loaded with 1 g cm -2 The baked carbon paper was clamped on the electrode clamp as the working electrode. The working electrode area was 1 cm 2 , then a platinum electrode was used as the auxiliary electrode, and Hg / HgO electrode in neutral (0.5M HHCO3) and alkaline (1 M KOH) electrolytes, and Hg2SO4 electrode in acidic (0.5 M K2SO4+H2SO4) electrolytes were used as reference electrodes; ② The performance of the material in the flow cell was tested using the constant current method, with the current density ranging from 50 to 1000 mA·cm -2 The test was carried out, and the test data was substituted into the calculation formula to calculate the formic acid Faraday efficiency of the catalyst of the method in the flow cell in acid, alkali and neutral solutions. The results are as follows Fig.10 (ac) Cu-doped BOC catalyst in neutral ( Fig.10 a) and alkaline solution ( Fig.10 a) 50~1000 mA·cm -2 The Faraday efficiency of formic acid in the range is above 96% ( Fig.10 c), 50~300 mA·cm in acidic solution -2 The Faradaic efficiency of formic acid in the range is also above 97%, indicating that the Cu-doped BOC catalyst has excellent performance in electrocatalyzing carbon dioxide to produce formic acid in the flow cell.
[0057] Example 7 The catalyst of Example 1 was used for measurement, and a working curve of the electrocatalytic carbon dioxide reduction stability in 1 M KOH solution was drawn: ① Use an electrochemical workstation to test with a three-electrode system and configure the catalyst to 5 mg mL -1 Ink, dripped on 4 cm 2 The carbon paper was loaded with 1 g cm -2 , the dried carbon paper is clamped on the electrode clamp as the working electrode, and the working electrode area is 1cm 2, then use the platinum electrode as the auxiliary electrode and the Hg / HgO electrode as the reference electrode; ② The material stability was tested using the constant current method. The reaction was carried out at a current of 50 mA. The results are as follows: Fig.10 d. The Cu-doped BOC catalyst can stably react for 50 h.
[0058] Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. Cu-doped Bi2O2CO3 nanosheet catalyst, characterized in that: The Cu salt and the Bi salt are mixed in a precursor solution and a nanosheet catalyst is synthesized by a hydrothermal method. The nanosheet catalyst is represented by the (011) and (110) crystal planes of Bi2O2CO3.
2. The method for preparing the Cu-doped Bi2O2CO3 nanosheet catalyst according to claim 1, characterized in that: Acetic acid, ammonia and water are used as solvents, copper nitrate and bismuth nitrate are dissolved in the solvents at the same time, and Cu-doped Bi2O2CO3 nanosheet catalysts are synthesized by hydrothermal method. Then, Cu-doped Bi2O2CO3 nanosheet catalyst powders are obtained through centrifugation, washing and drying.
3. The method for preparing the Cu-doped Bi2O2CO3 nanosheet catalyst according to claim 2, characterized in that: The following steps are involved: 1) Stir water, acetic acid and ammonia water in a reaction container to form a mixed solution 1, weigh copper nitrate and bismuth nitrate, add them to the mixed solution 1, and stir to form a mixed solution 2; 2) The mixed solution 2 is transferred to a reactor, and the reactor is placed in an oven for hydrothermal reaction. After the hydrothermal reaction, the mixture is naturally cooled, centrifuged, washed, and dried; 3) Take out the dried solid, grind it, and obtain Cu-doped Bi2O2CO3 nanosheet catalyst powder.
4. The method for preparing the Cu-doped Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 1), the volume ratio of water, acetic acid and ammonia water is 2: (0.9-1.1): (5.9-6.1), and the molar ratio of copper nitrate to bismuth nitrate is (0.5-4):
1.
5. The method for preparing the Cu-doped Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 2), the hydrothermal reaction temperature is 175-185°C and the reaction time is 11.5-12.5h.
6. The method for preparing the Cu-doped Bi2O2CO3 nanosheet catalyst according to claim 3, characterized in that: In step 2), water is used for washing, and the temperature for drying is 55-65° C. and the temperature is dried in an oven for 10-12 hours.
7. Use of the Cu-doped Bi2O2CO3 nanosheet catalyst as claimed in claim 1 in electrocatalytic carbon dioxide reduction.
8. Use of the Cu-doped Bi2O2CO3 nanosheet catalyst as claimed in claim 1 for electrocatalytic reduction of formic acid with carbon dioxide in neutral, alkaline and acidic electrolytes.
Citation Information
Cited By
COF-coated Bi-based catalyst as well as preparation method and application thereof
CN120366843A